Analysis of Children’s Footwear Relics From the Crypts in the Church in Radzyń Podlaski (18th–19th Century, East Poland) - Tomasz Kozłowski; Małgorzata (Acta Universitatis Lodziensis: Folia Archaeologica)
The study examines relics of leather shoes uncovered during the exploration of modern (18th–19th century) burials in the crypts of the church in Radzyń Podlaski, Eastern Poland. The shoes were found alongside the remains of two children, who were likely members of the noble class. Our analyses focused on the footwear’s size, shape, structure, construction, and finish. We also tried to document and interpret signs of wear observed on the preserved leather fragments. We believe this research contributes to a deeper understanding of the funeral customs of Poland’s former elite and provides insides into childhood during the 18th and 19th centuries.